PEMANFAATAN KULIT MANGGIS (GARCINIA MANGOSTANA L.) DALAM PEMBUATAN ES KRIM DENGAN VARIASI KONSENTRASI GUM XANTHAN - Rahmatun; Usman Pato; Evy Rossi (Fakultas Pertanian Universitas Riau, 2023)
Ice cream is a semi solid food made from milk which is very popular with the public. This study aimed to obtain the best concentration of xanthan gum as a stabilizer in the making of mangosteen skin ice cream. Making ice cream to produce attractive colors and contain then properties of mangosteen fruit skin is used. The study used a non factorial completely randomized design (CRD) with six treatments and three replications. The treatments in this study were the addition of xanthan gum concentrations namely P0 (0%), P1 (0.1%), P2 (0.2%), P3 (0.3%), P4 (0.4%), and P5 (0.5%). The results werestatistically analyzed using Analysis of Variance (ANOVA). The calculated F is greater than the F table, so it is continued with the Duncan’s Multiple Range Test (DMRT) at the 5% level. The results showed that the concentration of xanthan gum significantly affected (P<0.05%) total solids, melting point time, overrun, viscosity, and hedonic tests which included taste, softness and overall. However, the treatment xanthan gum concentrations did not significantly influence (P<0.05) the hedonic test namely color. The best treatment in this study was the addition of 0.5% xanthan gum (P5) to the manufacture of mangosteen skin ice cream. Mangosteen skin ice cream had a total solid of 39.80%, melting point time of 15.08 minutes, overrun of 26,73%, viscosity of 13,487.76 cP, and the hedonic score of the panelists was favorable.